Studies of solid state electrochromic devices based on PEO/siliceous hybrids doped with lithium perchlorate - Barbosa, P. C. (2006)
Sol–gel hybrid organic-inorganic networks, doped with a lithium salt, have been used as electrolytes in prototype smart windows. The work described in this presentation is focused on the application of these networks as dual-function electrolyte/adhesive components in solid-state electrochromic devices. The performance of multi-layer electrochromic devices was characterized as a function of the choice of precursor used to prepare the polymer electrolyte component and the guest salt concentration. The prototype devices exhibited good open-circuit memory, coloration efficiency, optical contrast and stability.